Features of Wear of Gears of Agricultural Machinery - Veselovsky Aleksandr; Troyanovskaya Irina; Syromyatnikov Yurii; Voinash Sergey; Malikov Vladimir; Zagidullin Ramil; Sabitov Linar (Acta Technologica Agriculturae, 2023)
The paper presents data on the resource and wear of the gears of agricultural tractor transmissions, on the basis of which the research problem and the novelty of the proposed methodology are formulated, based on the development and application of the stress state model of the gear, taking into account surface hardening. The methodology and calculation scheme for determining the power parameters of gearing are described in detail. In this case, the dependences and results of previous studies in the field of increasing the durability and reducing the wear of gears of transmission elements of vehicles of various functional purposes were used. To achieve this goal, the mathematical models of the stress state of gears are constructed without the presence of an external diffusion hardening coating and with a coating. Based on the simulation of the process of interaction of rubbing pairs of gears, the distribution of stresses in the contact zone over the surface layer of non-hardened and cemented to a depth of 1 mm gears, as well as the dependence of deflection on the thickness of the cemented layer and the deformation of the cemented layer during operation was established. Considering the research results given in literature, as well as those obtained on the basis of our own research, it should be noted that the analysis of gear stress state is an important direction in the study of the durability of gear units, the entire gearbox, and other gears of tractor transmissions and automotive technology at the present time. At the same time, the actual task is to establish the ratios of the allowable wear of gears and the limiting value of displacement of the centre distance, taking into account changes in the stress state scheme when using various types of coatings.